Days of rage: Introducing the NAVCO 3.0 dataset. (July 2018) - Chenoweth, Erica; Pinckney, Jonathan; Lewis, Orion
Although the empirical study of strategic nonviolent action has expanded in recent years, no current dataset provides detailed accounts of the day-to-day methods and tactics used by various nonviolent and violent actors seeking political change. We introduce the Nonviolent and Violent Campaigns and Outcomes (NAVCO) version 3.0 dataset, which assembles over 100, 000 hand-coded observations of nonviolent and violent methods in 21 countries around the world between 1991 and 2012. Researchers can use these data and their associated coding framework to (1) replicate or challenge existing findings about nonviolent and violent action; (2) test or uncover novel insights about the dynamics of violent and nonviolent action; and (3) recode existing protest events databases to capture specific variations in risk and disruption across event types. In particular, scholars can use these data to better understand which types of lower-level interactions between dissidents and regimes lead to large-scale mobilization; which sequences of nonviolent methods are most effective; and which types of spatial and participation diffusion yield the highest likelihood of success.